2014
DOI: 10.1152/ajpendo.00046.2014
|View full text |Cite
|
Sign up to set email alerts
|

Augmented expression and secretion of adipose-derived pigment epithelium-derived factor does not alter local angiogenesis or contribute to the development of systemic metabolic derangements

Abstract: Lakeland TV, Borg ML, Matzaris M, Abdelkader A, Evans RG, Watt MJ. Augmented expression and secretion of adipose-derived pigment epithelium-derived factor does not alter local angiogenesis or contribute to the development of systemic metabolic derangements. Am J Physiol Endocrinol Metab 306: E1367-E1377, 2014. First published April 23, 2014; doi:10.1152/ajpendo.00046.2014.-Impaired coupling of adipose tissue expansion and vascularization is proposed to lead to adipocyte hypoxia and inflammation, which in turn … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…PAI1 and PEDF have been shown as the inhibitors of angiogenesis process [31, 32]. However, a recent report described an inexplicable finding that overexpression of PEDF did not alter angiogenesis in mice adipose tissue [33]. Moreover, PAI1 has been reported to both positively and negatively regulate angiogenesis depending on the dosages [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PAI1 and PEDF have been shown as the inhibitors of angiogenesis process [31, 32]. However, a recent report described an inexplicable finding that overexpression of PEDF did not alter angiogenesis in mice adipose tissue [33]. Moreover, PAI1 has been reported to both positively and negatively regulate angiogenesis depending on the dosages [34].…”
Section: Discussionmentioning
confidence: 99%
“…Further studies are needed to determine the concentration of PAI1 contributing to cold-induced sWAT angiogenesis. Moreover, Lakeland et al has reported that instead of altering angiogenesis, the predominant role of PEDF is to modulate lipolysis positively [33]. It is possible that the cold exposure and CL treatment in sWAT utilize this mechanism to provide a fuel substrate to meet the increased energy demands.…”
Section: Discussionmentioning
confidence: 99%
“…Exogenous administration of recombinant PEDF to lean mice reduced insulin sensitivity during hyperinsulinemic-euglycemic clamp method which is the gold standard assessment of in vivo insulin sensitivity, whereas neutralisation of PEDF restored insulin sensitivity (Crowe et al, 2009). But on the other hand adipocyte generated PEDF enhanced lipolysis but did not contribute to the development of systemic metabolic derangements and improved metabolic derangements in obese type 2 diabetic rats (Lakeland et al, 2014;Matsui et al, 2014). The mechanism by which PEDF induces IR is not yet clear but acute administration of PEDF in rodents induces IR in vivo, and this onset of IR is accompanied by an increase in serum TNF and other cytokine levels.…”
Section: Pedf and Metabolic Diseasesmentioning
confidence: 98%
“…Moreover, the presence of PEDF in adipocyteconditioned media caused IR in myotubes, and these effects were reverted upon addition of PEDF-neutralising antibody. PEDF gene expression and secretion increased during differentiation of human preadipocytes (Lakeland et al, 2014). PEDF exclusively targets the initial adipogenic events such as repression of adipogenic transcription factors PPARγ and C/EBP-alpha and ERK1/2 activation (Yamagishi et al, 2008).…”
Section: Elevated In Metabolic Disordersmentioning
confidence: 99%
“…Adipocyte-specific PEDF transgenic mice (PEDF-aP2 mice) showed an increased adipocyte lipolysis compared with wild-type mice, confirming the effect of PEDF in regulating lipid metabolism. However, WAT-derived PEDF overexpression has no effect on the adipose vascularization, hypoxia and adipose inflammation in normal condition or after high-calorie diet [157]. There is no difference in glucose and insulin tolerance between PEDF-aP2 mice and control mice [157].…”
Section: Angiogenesis In Adipose Tissue Of Obesitymentioning
confidence: 99%